Opinion on the health and social functioning of nurses employed in a shift work system. Selected aspects - Stychno, Ewa; Zaręba, Justyna; Kulczycka, Kinga; Kosicka, Bogumiła (Journal of Education, Health and Sport, 2018)
Daily cycles of sleep/wake, is misaligned with behavioral patterns during shift work, leading to an increased risk of developing cardiovascular/metabolic/gastrointestinal disorders, some types of cancer, and mental disorders. The aim of this study was to understand the opinion on the health and social functioning of nurses employed in the shift work system.This study was conducted in 2016 on 100 selected nurses working in a shift system in one of the hospitals in Lublin. The average age of respondents was 41,54 years old. Results were collected with the author’s questionnaire.According to the nurses' opinion, work in a shift system has a negative impact on their health. Respondents complained primarily about problems with the digestive and circulatory systems. The number of nurses who feel the negative impact of shift work on their health increases with age and seniority. According to the respondents, shift work system causes them additional stress. Statistically significant dependence was shown between seniority in the shift system and an opinion on the negative impact of shift work on family life. The longer the shift work experience, the greater the percentage of respondents declaring its negative impact on family life. It is vital to implement measures reducing the negative effects of such a work system through the education of employees. It is also necessary to adapt the forms of work organization to the psychophysical possibilities of employed nurses.